The Wild one The Stanley Kramer Company, Inc. - Rooney, Frank; Brando, Marlon; Murphy, Mary, 1931-2011; Marvin, Lee (RCA/Columbia Pictures Home Video, 1986)
Johnny is the leader of a vicious biker gang which invades a small, sleepy California town. The leather-jacketed young biker seems hellbent for destruction until he falls for Kathie, a "good girl" whose father happens to be a cop.